The practice, challenges and awareness of residential solid waste management in the city of Al –Marj, Libya - Jaouda Hamad, Jaouda R.; Hanafiah, Marlia M.; Akbar John, B.; Sheikh, Hassan I. (Razi Publishing, 2017)
Solid waste management (SWM) in urban cities has always been a challenge to municipalities. Piles of garbage are seen on the roads and suburbs of highly populated neighbourhoods in the city of Al Marj, Libya. This study aimed at identifying the factors and barriers which influence solid waste management (SWM) in the city of Al Marj, Libya. The data was collected via a questionnaire survey and interview sessions with the residents of the city. A total of 700 questionnaires were distributed randomly; only 482 of these were filled up and returned. The results showed that the city of Al-Marj has a profound solid waste management and awareness problems that must be tackled immediately. The local authorities in charge of the SWM seemed to lack experience as well as facilities required for proper solid waste management. The residents also showed lack of awareness on recycling solid waste, however, they agreed to its importance. The over finding of the study indicated that numerous factors led to the solid waste management problem in the city of Al Marj, Libya.